Isolation and molecular characterization of subgroup J avian leukosis virus in native chicken breeds of China during 2022–2025 - Liu, Qi; Ji, Sifan; Li, Minghui; He, Lei; Ding, Ke; Yu, Zuhua; Chen, Jian (Frontiers in Microbiology, 2025)
Avian leukosis virus subgroup J (ALV-J) primarily infects poultry, especially chickens, where it induces immunosuppression and tumorigenesis. ALV-J has caused substantial economic losses worldwide and is prevalent among indigenous chicken breeds in China. In this study, we analyzed the genomic characteristics of ALV-J strains isolated from diseased liver tissue or anticoagulant blood samples collected from Lushi chickens, Central Plains cockfighting, and Hetian chickens between 2022 and 2025. The results showed that the nine isolates clustered within Clades 1.2 and 1.3, indicating that ALV-J is concurrently prevalent in multiple native chicken lineages. Compared with the ALV-J prototype strain HPRS-103, multiple specific functionally significant point mutations or deletion mutations occurred in the Gp85 protein and the 3′ untranslated region (3′ UTR) of all the isolates. These included the N123I mutation in the Gp85 protein, which stabilizes the Gp85 structure and expands the interaction interface, the D191N mutation suggesting the formation of a new N-glycosylation site, and the deletion mutations within the receptor-binding domain (RBD) that affect the efficiency of the binding between the virus and host cell receptors, as well as the reduced transmembrane (rTM) deletion mutation in the 3′ UTR that influences the viral replication ability, suggesting that the isolates analyzed may exhibit enhanced replication ability and pathogenicity. In addition, there are certain differences in the number of α-helices in the Gp85 proteins of these ALV-J strains, and these differences may have an impact on the interaction between the virus and host. The results of our study are conducive to enriching the epidemiological data of ALV-J and revealing the genetic evolution direction of ALV-J strains, which will provide a scientific basis for the prevention and control of avian leukosis.